(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: The aim of this study is to develop an in-situ gelling system for the effective delivery and sustained-release of levofloxacin in the treatment of anterior corneal infections. Material and Methods: Sodium alginate (SA) and hydroxypropyl methylcellulose (HPMC) were used to formulate in-situ gels (ISGs) with formulation codes F1-F12 and 0.5% levofloxacin solution was used as a control. The formulations were evaluated for clarity, pH, gelling capacity, drug content and antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa, Streptococcus pneumoniae and Staphylococcus aureus using the Kirby-Bauer disk diffusion test. The irritability and toxicity of select formulations were assessed using the Hen’s Egg Test, Chorioallantoic Membrane (HETCAM) assay. Results: The formulated ISGs were within pH range of 5.86 and 7.60. Formulation F7 (0.5% SA + 1.5% HPMC) had the highest gelling capacity and all ISGs had comparable activity against the tested organisms. Formulation F6 (1% HPMC + 1% SA) had the slowest release with approximately 60% release after 4 h, formulation F11 (1.5% HPMC + 2% SA) had the fastest release of 72% after 4 h while LVF solution (control) released 70% in 1 h. There was no significant (p = 0.101) change in the concentration of levofloxacin ISGs after storage at 25o C for 60 days and the HETCAM test confirmed the non-toxicity and non-irritability of the formulations. Conclusions: Levofloxacin in-situ gels formulated with SA and HPMC E5 LV are able to sustain the release of levofloxacin for 8 h and retain their effectiveness against relevant ocular bacterial infections.